Penggunaan Media PEMA (Papan Edukasi Main Anak) Dalam Meningkatkan Pemerolehan Kosakata Anak Usia 3-4 Tahun - Zahrina Amelia; Anisa Rahmadani (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
Early childhood needs to optimize various aspects of their development. One of them is the language aspect, the language skills of children can be seen from the way they communicate with other people. This needs to be supported by its vocabulary. At the age of 3-4 years, the average child knows 800 words, but still speaks in short sentences. If there is something complex to talk about, he will reveal it in two or three sentences. Currently, there are various kinds of game tools that are obtained by children, through educational play tools PEMA (children's play educational board) it is hoped that children can help children in acquiring vocabulary. The skill developed is the concept of printed letters. Children have the opportunity to interact with printed letters. Learn to recognize letters to achieve early reading skills for children. This study uses action research conducted on children aged 3-4 years. This study began by conducting a pre-test for the 5 children. Furthermore, parents document the use of PEMA media. The third is reflection of observation, reflection of documentation is interpreted in order to plan improvements that will be carried out in the next cycle. Activities are carried out repeatedly until the most appropriate one is found for each child. The results of the study are expected to increase children's vocabulary acquisition through PEMA media.Keywords - Pemerolehan, Kosakata, Media, Anak Usia Dini, PEMA